Использование возможностей Internet-ресурсов для развития профессионального сетевого взаимодействия школ города Лисаковска - Шоканова, Л.Ш.; Мурзабекова, О.В. (My University, 2016)
The article considers topical issues of organization and activities of the network of the professional community of teachers in a small town. Special attention is paid to the unity of content and forms of interaction, ways of engaging participants in the process of translation experience, focusing on the expected result: development of key skills of students.
Keywords: Online community; the website of the teachers of the city of Lisakovsk; networking